(untitled) (Texto & Contexto, 2018)
Objective: was to identify the social representations structure about AIDS among people with Human Immunodeficiency virus. Method: this is a descriptive research, based on the Central Core Theory of social representations. A free association test of words among 231 adults in antiretroviral therapy was applied. Software Ensemble de programmes permettantl’analyse dês evocations - EVOC2000® processed the evocations, generating a chart corresponding to the probable representation structure. Results: the elements disease, sadness, fear, death and transmission integrated the central nucleus. The peripheral system constituted itself more frequently by: prejudice, medicine and treatment, in the first periphery; difficult, preservative and healing, in the second periphery; bad, prevention and normal in the contrast zone. The central perceptions revealed shared elements since the onset of the infection. Conclusion: the peripheral system pointed to the need for continuous effort to coping with society and negative feelings, until they reach a cure